Strategy for Implementing Cooperative Professional Development Supervision in Improving the Quality of Teacher Learning - Sasgita Idris Soi; Besse Marhawati; Sulkifly Sulkifly (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2026)
This study aims to describe the Cooperative Professional Development (CPD) supervision strategy through clinical coaching to improve the quality of teacher learning at SMAN 1 Bonepantai . This study uses a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation with the principal, vice principal of the curriculum, and teachers participating in the clinical coaching. Then, they were analyzed interactively through the stages of collection, condensation, presentation, and conclusion drawing. The results show that the CPD supervision strategy was implemented through four stages: pre-observation, classroom observation, post-observation, and follow-up. The pre-observation stage involved discussions between teachers and the principal to determine the objectives, methods, media, and focus of learning development. Classroom observations were conducted collaboratively and supportively, emphasizing student engagement, classroom management, and the use of learning media. Post-observation provided space for reflection and constructive feedback, while follow-up was carried out through learning communities and the Teacher Learning Program. The impact of this strategy was seen in improved teaching practices, method innovation, more active student involvement, and a conducive and interactive classroom atmosphere. Overall, CPD supervision through clinical coaching effectively builds a reflective and collaborative culture and improves the quality of learning in a student-centered manner.